2013
DOI: 10.1159/000347003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CT Pulmonary Angiography in the Investigation of Unilateral Pleural Effusions

Abstract: Background: Pulmonary embolism (PE) is frequently cited as a common primary cause of unilateral pleural effusion, but in clinical practice appears to be uncommon. Objectives: In order to evaluate this observation, CT pulmonary angiography (CTPA) was performed in consecutive patients presenting to a single centre with a new uninvestigated unilateral pleural effusion and no clear cause and was supplemented by delayed-phase thoracic CT, optimized for visualization of the pleura. Methods: All patients underwent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 882 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…In a previous prospective study Hooper et al performed CTPA and late arterial phase CT (optimised for pleural imaging) in 141 patients with suspected PM. However the primary objective of this study was to assess the incidence of pulmonary emboli [7] and the diagnostic performance of CTPA for PM was not reported. In a small randomised study, Raj et al previously demonstrated better enhancement of the pleura utilising delayed phase (at 60–90 s post-contrast) CT acquisition [8], Therefore venous-phase CT should be requested in all patients with suspected PM, and this may have been used more frequently in the Hallifax study.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous prospective study Hooper et al performed CTPA and late arterial phase CT (optimised for pleural imaging) in 141 patients with suspected PM. However the primary objective of this study was to assess the incidence of pulmonary emboli [7] and the diagnostic performance of CTPA for PM was not reported. In a small randomised study, Raj et al previously demonstrated better enhancement of the pleura utilising delayed phase (at 60–90 s post-contrast) CT acquisition [8], Therefore venous-phase CT should be requested in all patients with suspected PM, and this may have been used more frequently in the Hallifax study.…”
Section: Discussionmentioning
confidence: 99%
“…Malignancy is an independent risk factors for venous thromboembolic disease(VTE) (36), increasing the overall risk 7-fold in patients with cancer, and 22 fold in patients with lung cancer (37). This study demonstrates that PEs are uncommon in unilateral effusions, however if it does occur, it is frequently associated with malignancy (35).…”
Section: Hypoalbuminaemiamentioning
confidence: 91%
“…The clinical diagnosis of pulmonary embolism (PE), particularly in the presence of a pleural effusion, can be difficult (35). A prospective trial investigating the incidence of PEs in consecutive patient with a unilateral effusions, with a dual phase CTPA (35), found the incidence of concurrent PEs was low (6.4%) and in no cases was it felt to be the leading cause of the effusion. PE was only clinically suspected in one case.…”
Section: Hypoalbuminaemiamentioning
confidence: 99%
“…29 However, a prospective study in which CT pulmonary angiography was performed in 141 consecutive patients with an undiagnosed effusion showed a pulmonary embolism in only nine patients (6.4%). 30 In no patient was the embolism thought to have caused the effusion. Thus, whether a pulmonary CT angiogram is warranted in all patients with an undiagnosed effusion remains to be determined.…”
Section: What Should Be Done If the Initial Evaluation Is Nondiagnostic?mentioning
confidence: 99%